Application of Information System in the Education Industry of Pakistan - Muhammad Kamran Jamil; Syed Asad Hussain (JISR Management and Social Sciences & Economics, 2003)
Technology is now a key factor in driving the economies of the world. Whether it is the field of pure a medical sciences; management or social science; technology's involvement and influence is there. Technology and its fast adoption have not only changed the traditional way of doing businesses but also directly affected the individual personalities, societies and nations. It has increased the efficiency, horizon the span of knowledge and strengthened the medium of information — seeking. Technology has its own merits and demerits but it depends on how it is used, when and where it is applicable and what technology may be used in specific situation or circumstances. Firstly, effective use of technology has brought in drastic changes in organizations comparing with the traditional way of doing business that lead to business processes redesigning and reengineering. Secondly due to globalization, transfer and adoption of technology is faster than it was before. Now the technology-based nations are successful and way ahead and have direct influence on the nations who are lacking behind in the adoption of technology. Now IT is widely used to develop information systems. Information System has played a major role in almost all the industries of Pakistan. Similar to other industries, educational institutions have also incorporated IT to develop their information systems to bring operational efficiency in academic administrative matters. The core function of any institution is to provide education to students. As Information Technology has changed the way of doing business, similarly, it has changed the traditional way of seeking knowledge. Unlimited educational information is available through Internet, which does not only facilitate students and researchers to get online information but also help them to share information and views across the borders. With the innovation of Internet technology and its wide usage, there is no physical barrier to information and knowledge. Due to removal of this barrier organizations’ emphasis towards hiring and employing “knowledge workers” has been increased. The secondary function, which supports the core function of any institute, is the academic administration. In addition to the curriculum, students are encountered with academic administrative matters before getting enrollment and even after it till completion of studies. Students need admission information, course curriculum details and __ filing enrolment procedures before getting registered in any institution’s program. Information which has direct involvement of students while studying such as availability of notes and reference materials, result, class schedule, accounts status, university’s programs, etc. There are other information which is not directly required by the students but institutions have to maintain it in order to provide efficient service to students such as data related to student admission formalities and submission of documents, registration into next semesters, result information, students’ fee payment status, faculty compensation or reimbursement, staff/HR information system, library information system, etc. If the institutions do not have such information systems applicable, they might do the same manually which has obviously resulted in delaying academic and administrative decisions.